Exhaled odorant measurement (EXOM) - A new approach to quantify the degree of in-mouth release of food aroma compounds - Büttner, Andrea; Schieberle, Peter (Lwt-Food Science and Technology, 2000)
Physiological factors influencing the transfer of volatiles from the oral cavity into the nose were studied. Special attention uns paid to the act of swallowing and to effects caused by mouth or tongue movements. The investigations,were carried out first with helium, then with aqueous odorant solutions using a novel approach called EXOM (exhaled odorant measurement)-concept. Therefore. the amounts of ethyl butanoate being exhaled through the nose during eating at distinct lime intervals were quantified by application of stable isotope dilution assays after trapping of the odorants on Tenax(TM). (C) 2000 Academic Press.
Keywords: retronasal flavour release; soft palate; velum; oral cavity; nasal cavity; pharynx